A Noble‐Metal‐Free Spintronic System with Proximity‐Enhanced Ferromagnetic Topological Surface State of FeSi above Room Temperature. Issue 3 (20th December 2022) - Hori, Tomohiro; Kanazawa, Naoya; Hirayama, Motoaki; Fujiwara, Kohei; Tsukazaki, Atsushi; Ichikawa, Masakazu; Kawasaki, Masashi; Tokura, Yoshinori
Abstract: Strongly spin–orbit coupled states at metal interfaces, topological insulators, and 2D materials enable efficient electric control of spin states, offering great potential for spintronics. However, there are still materials challenges to overcome, including the integration into advanced silicon electronics and the scarce resources of constituent heavy elements of those materials. Through magneto‐transport measurements and first‐principles calculations, here robust spin–orbit coupling (SOC)‐induced properties of a ferromagnetic topological surface state in FeSi and their controllability via hybridization with adjacent materials are demonstrated. In comparison to the case of its naturally oxidized surface, the ferromagnetic transition temperature is greatly increased beyond room temperature and the effective SOC strength is almost doubled at the surface in proximity to a wide‐bandgap fluoride insulator. Those enhanced magnetic properties enable room‐temperature magnetization switching, being applicable to spin–orbit torque based spintronic devices. Realization of strong SOC in the noble‐metal‐free silicon‐based compound will accelerate spintronic applications. Abstract : Room‐temperature ferromagnetism and strong spin–orbit coupling are realized at a novel topological surface state of the nonmagnetic insulator FeSi by exploiting the proximity effect from a wide‐bandgap insulator. A consequent spintronic functionality, that is, current‐induced magnetization switching at room temperature, shows great potential for the application of proximity‐controlled light‐element topological materials as noble‐metal‐free devices.